Workstation Risk Factors for Work-related Musculoskeletal Disorders Among IT Professionals in Indonesia - Tofan Agung Eka Prasetya; Nurul Izzah Abdul Samad; Aisy Rahmania; Dian Afif Arifah; Ratih Andhika Akbar Rahma; Abdullah Al Mamun (Korean Society for Preventive Medicine, 2024)
Objectives: This study aimed to identify workstation factors influencing work-related musculoskeletal disorders (WMSDs) among information technology (IT) professionals in Indonesia. Methods: A cross-sectional study was conducted among 150 IT workers at small-enterprise companies who were randomly selected across East Java, Indonesia. The data were modeled using multiple linear regression, with a 95% level of confidence for determining statistical significance. Results: The respondents reported that the neck had the highest level of discomfort and was the most at risk of WMSDs, followed by the lower back, right shoulder, and upper back. Screen use duration (p=0.040) was associated with whole-body WMSDs, along with seat width (p=0.059), armrest (p=0.027), monitor (p=0.046), and a combined telephone and monitor score (p=0.028). Meanwhile, the factors significantly related to the risk of WMSDs in the hands and wrist were working period (p=0.039), night shift (p=0.024), backrest (p=0.008), and mouse score (p=0.032). Conclusions: Occupational safety authorities, standards-setting departments, and policymakers should prioritize addressing the risk factors for WMSDs among IT professionals.